2009
DOI: 10.1111/j.1600-0609.2009.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of 20 agents in different prognostic subgroups of chronic lymphocytic leukemia – rolipram and prednisolone active in cells from patients with poor prognosis

Abstract: Prednisolone and rolipram are interesting for further studies in CLL with inferior prognosis. The study can also be considered a basis for future efforts to find drugs active in subsets of CLL patients that are resistant to conventional therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…This is in agreement with what has been previously described using prednisone and methylprednisolone (32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with what has been previously described using prednisone and methylprednisolone (32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 93%
“…In CLL, it has been found that dexamethasone up-regulates mRNA and protein expression of the pro-apoptotic BH3-only gene Bim (31). Of note, cell death induced by glucocorticoids is higher in CLL with unmutated IGHV genes (UCLL)/high ZAP-70 expression than in cases with mutated IGHV genes (MCLL)/low ZAP-70 (32)(33)(34)(35), although the molecular mechanisms that could explain these differences have not been uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro drug resistance correlated with the presence of 17p and 11q deletion, as documented in other small studies, 13, 14 but also with unmutated IGHV genes. The TRAC assay LC 90 (fludarabine), together with 17p and 11q deletion and IGHV gene mutation status was an independent variable predicting PFS.…”
supporting
confidence: 81%
“…11, 12, 13, 14 These results suggested that in vitro drug sensitivity of CLL cells is independent of IGHV gene mutation status. 11, 14 However, as expected from clinical experience, in vitro sensitivity to fludarabine and chlorambucil was lower in patients with ATM/TP53 deletions 13, 14 and higher in patients with low-beta-2 microglobulin, longer lymphocyte doubling-time and lack of TP53 deletion. 12 The in vitro prednisolone sensitivity of TP53 -deleted cases correlated with the reported in vivo sensitivity.…”
mentioning
confidence: 89%
“…When high throughput screening technology was employed to identify agents that synergize with dexamethasone to inhibit proliferation of MM.1S and DLBCL cells, the compounds identified to produce the greatest amount of synergy were adenosine A2A receptor agonists and PDE 2,3,4, and 7 inhibitors ( Rickles et al, 2010 ). In a study examining the in vitro antileukemic activity of 20 different anticancer agents against tumor cells from CLL patients aimed at identifying agents active in poor-prognostic subgroups, it was found that prednisolone and rolipram displayed high CLL specificity and high activity in CLL with unmutated IGHV genes and when prednisolone and rolipram were combined they displayed considerable synergy against these CLL cells, thereby identifying rolipram as an agent with high activity in cells from patients with poor prognosis ( Lindhagen et al, 2009 ). Recent studies from the Lerner laboratory showed that rolipram induced apoptosis of both IGHV unmutated and mutated CLL cells, suggesting that cAMP signaling may abrogate a TLR9-mediated survival signal in prognostically unfavorable IGHV unmutated CLL cells, and indicating that PDE4 inhibitors may well be of clinical utility in CLL or autoimmune diseases that are driven by TLR-mediated signaling ( Tan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%